Fiber length and attenuation measurement by utilizing polarized beam splitter and fiber coupler in optical time domain reflectometer - Jahanadan, Subramaniam (Faculty of Science, 2009)
In this study, attention was made to measure the length of the fiber and the coefficient of the fiber attenuation using novel configurations. Laser diode with a fundamental wavelength of (808 ± 10) nm with a maximum power of 50 mW was employed. The measurement was made by using a polarized beam splitter and a beam coupler. The laser was operated in pulsed mode with a 75 ns pulse width which delivered an average power of 15 mW and continuous mode with a 50 % duty cycle. A preamplified Si PIN photodetector was used to detect the backscattered light. The fiber length measurement was compared utilizing a conventional Anritsu OTDR with an 850 nm wavelength. The length of the fiber obtained is 1313.99 m with a deviation of 0.46 % from a beam splitter measurement with a corresponding attenuation coefficient of 2.65 dBkm-1 with a deviation of 16.22 % and 1303.89 m with a deviation of 0.38 % for the beam coupler with the corresponding attenuation coefficient of 2.58 dB.km-1 with a deviation of 13.16 %